Investigation of yields and qualities of pyrolysis products obtained from oil palm biomass using an agitated bed pyrolysis reactor - Arkom Palamanit; Phonthip Khongphakdi; Yutthana Tirawanichakul; Neeranuch Phusunti (Biofuel Research Journal, 2019)
Oil palm biomass is a non-woody lignocellulosic biomass that has a high potential at the south of Thailand for biofuels and bioenergy applications. Pyrolysis of oil palm biomass to produce biofuels such as bio-oil, biochar, and pyrolysis gas is still challenging. The aim of this study was therefore to investigate the yields and qualities of pyrolysis products obtained from oil palm trunk (OPT), oil palm fronds (OPF), and oil palm shell (OPS) using an agitated bed pyrolysis reactor. These biomasses were pyrolyzed at pyrolysis temperatures of 400, 450, and 500°C while the other operating parameters were fixed. The results showed that the different types of oil palm biomass and pyrolysis temperatures affected the product yields and qualities. The OPF pyrolyzed at 500°C provided the highest liquid yield. The liquid product contained a relatively high water content with a low pH value, leading to highly-oxygenated compounds as indicated by gas chromatography-electron ionization/mass spectroscopy technique (GC-EI/MS). The higher heating value (HHV) of the liquid product was 18.95-22.52 MJ/kg. The biochar had a relatively high HHV ranging from 25.14 to 28.45 MJ/kg. Scanning electron microscopy (SEM) indicated that the resultant biochar had a porous structure surface with a surface area of 1.15-4.43 m2/g as indicated by BET. The pyrolysis gas contained a low composition of combustible gases, leading to a low HHV.